2020
DOI: 10.1111/jcpp.13189
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to polycyclic aromatic hydrocarbons modifies the effects of early life stress on attention and Thought Problems in late childhood

Abstract: Background: Risk for childhood psychopathology is complex and multifactorial, implicating direct and interacting effects of familial and environmental factors. The role of environmental neurotoxicants in psychiatric risk is of growing concern, including polycyclic aromatic hydrocarbons (PAH), common in air pollution. Prenatal PAH exposure is linked to adverse physical, behavioral, and cognitive outcomes as well as increasing psychiatric risk. It is unclear whether environmental exposures, like PAH, magnify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 106 publications
(123 reference statements)
3
33
0
Order By: Relevance
“…Associations with anxious/ depressed behaviour were found in 3/4 studies(Perera et al 2012;Perera et al 2011;Perera et al 2013) (OR=8.89, 95%CI, 1.7 to 46.51; OR= 8.14, 95%CI, 1.21 to 54.94; OR=1.7, 95%CI, 1.08 to 2.68 respectively) with no association found byPagliaccio et al (2020). 3/5 studies reported negative effect on child attentiveness(Perera et al 2018;Pagliaccio et al 2020;Perera et al 2012) (OR=1.34, 95%, 0.85 to 1.83; OR= 2.02, 95%,…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Associations with anxious/ depressed behaviour were found in 3/4 studies(Perera et al 2012;Perera et al 2011;Perera et al 2013) (OR=8.89, 95%CI, 1.7 to 46.51; OR= 8.14, 95%CI, 1.21 to 54.94; OR=1.7, 95%CI, 1.08 to 2.68 respectively) with no association found byPagliaccio et al (2020). 3/5 studies reported negative effect on child attentiveness(Perera et al 2018;Pagliaccio et al 2020;Perera et al 2012) (OR=1.34, 95%, 0.85 to 1.83; OR= 2.02, 95%,…”
mentioning
confidence: 89%
“…11 included cohorts from the USA. 6 selected participants from the Columbia Centre for Children's Environmental Health cohort, however each selected different subgroups of the population, and measured different outcomes (Perera et al 2006;Perera et al 2018;Perera et al 2015;Perera et al 2012;Perera et al 2011;Pagliaccio et al 2020). 2 studies selected a subgroup of participants from the National Health and Nutrition Examination Survey 2001-2002 (NHANES) (Best et al 2016), 1 of which included additional participants from the NHANES 2003-2004 cohort (Abid et al 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations